Passion and Quest for Quality in Education - Pandey, Shiv Ram (Journal of Social Work and Science Education, 2023)
The paper presents the passion and quest for quality in education. The purpose of this paper is to explore quality benchmark in education. It defines quality and demonstrates different dimensions of quality in education. It also presents why quality education is important to the learners. It is a theoretical article. The available relevant literature has been reviewed, analyzed and linked with life, learning, social justice and quality education benchmark. Therefore, quality education is the evaluation of educational level. It definitely comes from the quality of person who are educated. It also implies to the developing of basic qualities on child and providing training in a relevant field. Hence, it is said that, quality education refers to the relevancy of knowledge; it is the character of the set of elements in the input, process and output of education system that provides services satisfy in both internal and external strategic consistencies in quality education by meeting their explicit and implicit expectations. Stakeholders of education such as teachers, students, parents, curriculum developers, syllabus designers and textbook writers are responsible to strive, struggle, survive and thrive with quality in education.